Manipulating Ferroelectric Polarization and Spin Polarization of 2D CuInP2S6 Crystals for Photocatalytic CO2 Reduction - Chiang, Chun-Hao; Lin, Cheng-Chieh; Lin, Yin-Cheng; Huang, Chih-Ying; Lin, Cheng-Han; Chen, Ying-Jun; Ko, Ting-Rong; Wu, Heng-Liang; Tzeng, Wen-Yen; Ho, Sheng-Zhu; Chen, Yi-Chun; Ho, Ching-Hwa; et al. (Journal of the American Chemical Society, 2024)
Manipulating electronic polarizations such as ferroelectric or spin polarizations has recently emerged as an effective strategy for enhancing the efficiency of photocatalytic reactions. This study demonstrates the control of electronic polarizations modulated by ferroelectric and magnetic approaches within a two-dimensional (2D) layered crystal of copper indium thiophosphate (CuInP2S6) to boost the photocatalytic reduction of CO2. We investigate the substantial influence of ferroelectric polarization on the photocatalytic CO2 reduction efficiency, utilizing the ferroelectric-paraelectric phase transition and polarization alignment through electrical poling. Additionally, we explore enhancing the CO2 reduction efficiency by harnessing spin electrons through the synergistic introduction of sulfur vacancies and applying a magnetic field. Several advanced characterization techniques, including piezoresponse force microscopy, ultrafast pump-probe spectroscopy, in situ X-ray absorption spectroscopy, and in situ diffuse reflectance infrared Fourier transformed spectroscopy, are performed to unveil the underlying mechanism of the enhanced photocatalytic CO2 reduction. These findings pave the way for manipulating electronic polarizations regulated through ferroelectric or magnetic modulations in 2D layered materials to advance the efficiency of photocatalytic CO2 reduction.Manipulating electronic polarizations such as ferroelectric or spin polarizations has recently emerged as an effective strategy for enhancing the efficiency of photocatalytic reactions. This study demonstrates the control of electronic polarizations modulated by ferroelectric and magnetic approaches within a two-dimensional (2D) layered crystal of copper indium thiophosphate (CuInP2S6) to boost the photocatalytic reduction of CO2. We investigate the substantial influence of ferroelectric polarization on the photocatalytic CO2 reduction efficiency, utilizing the ferroelectric-paraelectric phase transition and polarization alignment through electrical poling. Additionally, we explore enhancing the CO2 reduction efficiency by harnessing spin electrons through the synergistic introduction of sulfur vacancies and applying a magnetic field. Several advanced characterization techniques, including piezoresponse force microscopy, ultrafast pump-probe spectroscopy, in situ X-ray absorption spectroscopy, and in situ diffuse reflectance infrared Fourier transformed spectroscopy, are performed to unveil the underlying mechanism of the enhanced photocatalytic CO2 reduction. These findings pave the way for manipulating electronic polarizations regulated through ferroelectric or magnetic modulations in 2D layered materials to advance the efficiency of photocatalytic CO2 reduction.